PENERAPAN MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN PAPAN ENERGI UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS IV SDN 3 BLIMBING KIDUL - Sa’adah, Amaliya Lailatus; Alviana, Kharisma Yogi; Ahsani, Eva Luthfi Fakhru (Prodi PGMI STIT Sunan Giri Bima, 2022)
This study aims to increase the activeness of students in science learning by using the Teams Games Tournament (TGT) cooperative learning model with the help of the media